A Case of Alopecia Areata Treated with Bee Venom and Carthami Flos Herbal Acupuncture - Kim Kyung-Woon; Seo Jung-Chul; Lee Kyung-min; Lim Seong-chul; Jung Tae-young; Han Sang-won (Korean Pharmacopuncture Institute, 2004)
Objective : Alopecia areata is a common disease and the difficulty of its medical management is well known. This study was designed to investigate the effect of bee venom and Carthami Flos herbal acupuncture. Methods : The patient was managed by bee venom, carthami-flos herbal acupuncture and General acupunture. Herbal acupuncture was injected subcutaneously into the lesion. We checked involvement in plaque, according to evaluation of the effect on alopecia areata. Result : After 5 month of treatment, the lesion had been replaced with new terminal hair. Evaluation of the effect on alopecia areata The score changed from 0 to 3 point. Conclusion : These result suggest that bee venom and Carthami Flos herbal acupuncture has good effect on alopecia areata. But further studies are required to concretely prove the effectiveness of bee venom and Carthami Flos herbal acupuncture for treating alopecia areata.